Hubungan antara Perilaku Pengguna Aplikasi Tiktok dengan Tingkat Harga Diri pada Siswa SMA Negeri 2 Semarang - Himatul Millaini Assyifa; Wigyo Susanto; Dwi Heppy Rochmawati (Lembaga Pengembangan Kinerja Dosen, 2026)
Background: TikTok usage among adolescents is increasing and has the potential to impact psychological aspects, particularly self-esteem. Adolescents, who are in the stage of developing their identity, are vulnerable to the influence of interactions and social comparisons on social media. Therefore, this study aims to determine the relationship between TikTok usage behavior and self-esteem levels in students at SMA Negeri 2 Semarang. Method: This study employed a descriptive correlational research design with a cross-sectional approach. The population consisted of 424 students from grade 11 at SMA Negeri 2 Semarang. Sampling was conducted using the Simple Random Sampling technique, resulting in a total sample of 206 respondents, determined by the Slovin formula. Bivariate analysis was carried out using the Spearman Rank Correlation test. Result: The results of the Spearman Rank statistical test showed a correlation coefficient (r) of -0.412 with a significance value of 0.000. The negative correlation indicates an inverse relationship between TikTok usage behavior and students’ self-esteem levels, meaning that the higher the intensity of TikTok use, the lower the self-esteem of the students. The correlation coefficient of 0.412 falls within the category of a moderate relationship. Conclusion: There is a significant relationship between TikTok usage behavior and self-esteem levels among high school students.